2011
DOI: 10.1002/chem.201100216
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Modulation of Peptoids: Synthesis and Conformational Studies on Partially Constrained Derivatives

Abstract: The high conformational flexibility of peptoids can generate problems in biomolecular selectivity as a result of undesired off-target interactions. This drawback can be counterbalanced by restricting the original flexibility to a certain extent, thus leading to new peptidomimetics. By starting from the structure of an active peptoid as an apoptosis inhibitor, we designed two families of peptidomimetics that bear either 7-substituted perhydro-1,4-diazepine-2,5-dione 2 or 3-substituted 1,4-piperazine-2,5-dione 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 74 publications
1
33
0
Order By: Relevance
“…Moreover, P26 was less active in BSC-1 cells (29.0 AE 0.4 mm), whereas P9 exhibited similar activities in both cell lines (IC 50 in HeLac ells 4.7 AE 0.3 mm, IC 50 in BSC-1 cells 4.7 AE 0.4 mm). Induction of apoptosis in the caspase3/7 activity was observed at 5 mm P26 ( Figure 3D).…”
Section: Structure-activity Relationship Studiesmentioning
confidence: 59%
See 3 more Smart Citations
“…Moreover, P26 was less active in BSC-1 cells (29.0 AE 0.4 mm), whereas P9 exhibited similar activities in both cell lines (IC 50 in HeLac ells 4.7 AE 0.3 mm, IC 50 in BSC-1 cells 4.7 AE 0.4 mm). Induction of apoptosis in the caspase3/7 activity was observed at 5 mm P26 ( Figure 3D).…”
Section: Structure-activity Relationship Studiesmentioning
confidence: 59%
“…On the basis of our previous experience, [49][50][51][52] the constriction of conformational mobility should improve activity and selectivity of these peptoid hits.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…A hit compound (1) was obtained [6], and structural studies of 1 showed the presence of cis/trans isomers of the tertiary amide bond exchanging at low rates ( Fig. 1) [7]. The occurrence of these cis/trans isomers has led us to freeze the cis and trans configuration by isosteric substitution using a triazole moiety [8].…”
Section: Introductionmentioning
confidence: 99%